C2-selective alkylation of pyridines by rhodium–aluminum complexes. (27th August 2021) - Hara, Naofumi; Aso, Koki; Li, Qiao-Zhi; Sakaki, Shigeyoshi; Nakao, Yoshiaki
Abstract: A C2- and mono-selective alkylation of various pyridines and azines with unactivated alkenes and vinylarenes using a heterobimetallic Rh–Al catalyst is reported. The use of aliphatic alkenes exclusively affords the linear alkylation products, while vinylarenes mainly afford branched alkylation products. The details of the reaction mechanism are revealed by DFT calculations: the reductive elimination of the products is rate-determining, which is consistent with the experimental results. The origin of the linear/branched selectivity is elucidated based on deformation/interaction analysis. Graphical abstract: Image 1